Роль показателей точности и быстродействия систем автоматического регулирования в энерго- и ресурсосберегающих технологиях - Канюк, Геннадий Иванович; Близниченко, Елена Николаевна (НТУ "ХПИ", 2006)
У статті показана роль та засоби підвищення частоти регулювання та швидкодії ЕГСР, а також залежність річного економічного ефекту від підвищення ККД енергоблоку. Доведені результати синтезу прецизійного швидкодіючого регулятору САР Ч та П на основі рішення зворотної задачі динаміки об’єкту управління та його загальна структурна схема.

In a paper the role and ways of increase of accuracy of regulation and speed electrohydraulic regulating systems (EHRS), and also dependence of annual economic benefit on increase of efficiency of the generating set is shown. Results of synthesis of a precision high-speed regulator of automatic regulating systems of frequency and power are given on the basis of the decision of a return problem of dynamics of object of management and its general block diagram.
Role of parametrs of accuracy and speed of systems of automatic control in energy- and resource keeping technologies
Keywords: электронно-гидравлические следящие системы; КПД; мощность; электрические приборы; двигатели внутреннего сгорания; регулятор сигнала